1987
DOI: 10.1002/clc.4960100303
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional flow in congenital ventricular septal defect: A doppler echocardiographic study

Abstract: Summary:The purpose of this study was to demonstrate the value of combined two-dimensional and pulsed Doppler echocardiography (echo) in localizing and recording bidirectional flow in congenital ventricular septal defect. Eight children, aged 8 months to 16 years, with clinical signs of a ventricular septal defect, underwent twodimensional and pulsed Doppler echo study prior to cardiac catheterization. The ventricular septal defect was documented anatomically by two-dimensional echo in all eight patients. Flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Although VSD is a congenital disease, it can be considered a chronic disease for some adult patients due to imperfect diagnosis and treatment conditions and insufficient attention. The hemodynamic changes caused by the long-term existence of congenital heart malformations also leads to structural changes in the heart to some extent [13]. The results of this study showed that some patients' left ventricular size before treatment was at the high limit of the normal value, which was associated with left-to-right shunt changes in cardiac blood flow caused by VSD.…”
Section: Discussionmentioning
confidence: 70%
“…Although VSD is a congenital disease, it can be considered a chronic disease for some adult patients due to imperfect diagnosis and treatment conditions and insufficient attention. The hemodynamic changes caused by the long-term existence of congenital heart malformations also leads to structural changes in the heart to some extent [13]. The results of this study showed that some patients' left ventricular size before treatment was at the high limit of the normal value, which was associated with left-to-right shunt changes in cardiac blood flow caused by VSD.…”
Section: Discussionmentioning
confidence: 70%
“…Volume assessment of shunt using VTI has been validated previously. 13 This study builds on clinical application of this methodology. However, we did not use intra-cardiac invasive measurements at rest/stress to justify our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Tasuku Sato, MS 1) , Toru Hashimoto, MD, PhD 2,4) *, Yusuke Ishikawa, MD 2) , Takeo Fujino, MD, PhD 2) , Ichiro Sakamoto, MD 2) , Taiki Higo, MD 2) , Akira Shiose, MD, PhD 1,3) , Hiroyuki Tsutsui, MD, PhD 2)…”
Section: Defect In a Patient With Left Ventricular Assist Devicementioning
confidence: 99%
“…It has been reported that to-and-fro or R-L shunt in diastole was documented in some patients with VSD, who had large VSD or were accompanied by severe pulmonary hypertension. 4,5 The finding of continuous R-L shunt across morphologically small VSD without advanced pulmonary hypertension might be unique to patients with LVAD.…”
Section: )mentioning
confidence: 99%